Analysis of The Effectiveness of Implementation SAP R/3 In PT. ABC - WANGKAR, Anneke (PT Keberlanjutan Strategis Indonesia, 2022)
This research analyses the effectiveness of SAP R/3 toward user satisfaction in using the application. The research is in PT ABC, manufactured in paper and tissue products. The research questions of this research are: